From Maqasid al-Shariah to the Sustainable Development Goals: Repositioning Islamic Economics as a Framework for Inclusive and Sustainable Human Development - Ismail Iliyasu Danladi; Adamu Abubakar Muhammad; Aishatu Attahiru Bappah; Adam Muhammad Ardo; Muhammad Romi; Abdullah A. Afifi (Journal of Regional Development and Technology Initiatives, 2025)
This paper examines the potential of the 'Maqasid al-Shariah' to serve as a moral and institutional framework that contributes towards meeting the Sustainable Development Goals (SDGs). This paper, aims to present the Islamic economic system as a comprehensive framework to promote inclusive growth, social justice and sustainable human well being and thus provides an Islamic integrative framework to tackle the global Sustainable development challenges. This research adopts qualitative approach of research, that mostly depends on literature review, which encompasses the study of classical sources of Islamic literature as well as current publications on Islamic Economics, Maqasid al-Shariah, international development policy, social finance. A conceptual and analytical technique would be used to build on current body of research, to conceptualize the bridge between the principles of Islamic Economics and a broader set of global sustainable development goals. The result shows that Islamic economics has a moral and institutional foundation towards sustainable development; greater than the current economic growth focused on development models. Several principles in Islamic economics like, justice (adl), public interest (maslahah), co-operation and assistance (takaful), trusteeship (khilafah) as well as moderation (wasatiyyah) are in close correlation with the aspirations of SDGs, and take the SDGs further with moral and spiritual context. Islamic social finance instruments like Zakah, Waqf and Sadaqah can also serve as significant tools to implement SDGs in the context of poverty eradication, financial inclusion, education and health services, as well as environmental health and resilience of the economy to tacle the future challenges. Based on the above discussion, the paper proposes a conceptual model titled, 'Maqasid-SDG Integrated Development framework (MSIDF)', that could be utilized as guidelines to align the Islamic economics institution to achieving a sustainable and decent human well being. The study contributes to the existing body of knowledge by changing the scope of the study from an examination of Islamic finance to the exploration of the potential of Islamic economics to provide a comprehensive ethical framework for a sustainable and inclusive development in the world.